Pengaruh Corporate Social Responsibility Terhadap Tax Avoidance Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Stefhanie Stefhanie; Sari Dewi Dewi (Komunitas Dosen Indonesia, 2022)
This research was conducted because of the contrasting desires between the government and taxpayers. The desire to optimize tax payments is carried out by the government while the desire to minimize tax payments is carried out by taxpayers because tax payments can reduce company income, thus giving rise to the intention of tax avoidance practices. The purpose of this study was to determine the effect of corporate social responsibility on tax avoidance in 240 Indonesian stock exchange companies from 2017-2021. Tax avoidance uses the current etr formula as a measure of the variable. This study uses quantitative data with the determination of the sample used is the purposive sampling method. The data analysis technique used is panel regression and uses two programs for data management. The results of the influence of variables in research on tax avoidance, namely corporate social responsibility as an independent variable has an insignificant effect, the control variable is company size, net cash from operating activities has a significant negative effect, sales growth has a significant positive effect, return of assets, leverage, plant, property and equipment, and intangible assets have a insignificant effect